Variation in Enamel Formation Genes Influences Enamel Demineralization In Vitro in a Streptococcus mutans Biofilm Model - Pang, Liangyue; Zhi, Qinghui; Zhuang, Peilin; Yu, Lixia; Tao, Ye; Lin, Huancai (Frontiers in Physiology, 2017)
Genetic studies have shown that variations in enamel formation genes are associated with caries susceptibility. The aim of this study was to test in vitro whether variants in these genes are associated with dental enamel demineralization in a Streptococcus mutans biofilm model. DNA and enamel samples were obtained from 213 individuals. DNA was extracted from saliva, and 16 single nucleotide polymorphisms were analyzed. The physical and chemical properties of sound enamel samples and the mineral loss and the lesion depth of the demineralized enamel samples under cariogenic challenge were analyzed. Microhardness, enamel chemicals, mineral loss and demineralization depth were compared between different genotypes at each single nucleotide polymorphism. The GG genotype of TUFT1 (rs17640579) and the GT genotype of MMP20 (rs1612069) exhibited increased microhardness (p = 0.044 and 0.016, respectively). The GG genotype of AMBN (rs7694409) had a higher magnesium level, while the CT genotype of TFIP11 (rs2097470) had a lower magnesium level (p = 0.044 and 0.046, respectively). The GT genotype of MMP20 (rs1612069) had a higher calcium level (p = 0.034). The GG genotype of AMBN (rs13115627), the AG genotype of ENAM (rs12640848) and the AA genotype of MMP20 (rs2292730) had a lower phosphorus level (p = 0.012, 0.006 and 0.023, respectively). The GG genotype of AMBN (rs13115627) was also associated with a higher calcium-phosphorus ratio (p = 0.034). Individuals with the CC genotype of TFIP11 (rs134143) exhibited significantly more mineral loss (p = 0.011) and a deeper lesions (p = 0.042). Individuals with the TT genotype of TFIP11 (rs2097470) had more mineral loss (p = 0.018). Individuals with the GG genotype of TUFT1 (rs17640579) exhibited a shallower demineralization depth (p = 0.047). Individuals with the GT genotype of MMP20 (rs1612069) exhibited a shallower demineralization depth (p = 0.042). Individuals with the GG genotype of ENAM (rs12640848) exhibited less mineral loss (p = 0.01) and a shallower demineralization depth (p = 0.03). Genetic variations in TFIP11, TUFT1, MMP20 and ENAM influenced enamel demineralization in a Streptococcus mutans biofilm model.